Kombinasi seramik dan bahan buangan industri dalam penghasilan karya seni - Brazil, ak. Mission. (Universiti Malaysia Sarawak, (UNIMAS), 2007)
Nowadays, our world is suffering heavily from the polution caused by the heavy industrialization activities. Some of these waste materials are disposed of into inappropriate places such as rivers, oceans and human domains. This work is a mean of self-protest towards these untoward and hazardous activities that are harmful to the environment and human kind.